После тебя: [роман] / Джоджо Мойес - Мойес Джоджо (Иностранка, 2017)
Экземпляры: ф-4 (20180723) / Инвентарный номер: 52336 / Цена: 321.60 / Сис.шифр: И(Англ) / Авт.знак: М 74 / ГРНТИ: 17.82 / ББК: 84(4Вел)